ANALISIS PENGARUH BRAND EXPERIENCE TERHADAP BRAND PERCEIVED VALUE, BRAND SATISFACTION, DAN BRAND LOYALTY - I Gede Putu Pranadata (University of Merdeka Malang, 2017)
This research aims to analyze the influence of brand experience on brand perceived value, brand satisfaction, and brand loyalty in one stop carcare service industry in Malang City and also to analyze how the role of brand perceived value and brand satisfaction in mediating the influence of brand experience on brand loyalty in one stop carcare service industry in Malang. This type of research is an explanatory research and sampling method used is non probability sampling with sampling purposive sampling technique. The sample of research is 200 consumer of D2 Autocare and Autowash Malang and the data obtained is analyzed with Structural Equation Modeling (SEM) using Smart Modeling PLS version 3.0 program. The results show that brand experience directly does not significantly affect brand loyalty but brand experience significantly influence brand loyalty when mediated by brand perceived value and brand satisfaction that acts as a perfect mediation in this research. This indicates that the D2 should continue to improve brand experience, brand perceived value, and brand satisfaction to increase brand loyalty from consumers DOI : https://doi.org/10.26905/jbm.v4i2.1702